Environmental sustainability of palm oil exports in Riau Province: Evidence from deforestation, carbon emissions, and RSPO certification - Rini Nizar; Latifa Siswati; Erick Gunawan Bahar (Agriekonomika, 2026)
The rapid expansion of Indonesia’s palm oil industry has raised concerns regarding deforestation and carbon emissions, particularly in major producing regions such as Riau Province. This study aims to examine the relationship between palm oil exports and environmental sustainability by considering deforestation, carbon emissions, and RSPO certification during 2013–2023. The study employs a quantitative approach using secondary data, descriptive analysis, and regression-based assessment. The findings indicate that increases in palm oil export values are not consistently accompanied by higher deforestation, although export growth remains associated with environmental pressure through carbon emissions. Meanwhile, RSPO-certified plantation areas tend to be associated with lower deforestation and carbon emissions. These results suggest that environmental outcomes in the palm oil sector are influenced not only by export performance but also by sustainability governance mechanisms. The study recommends strengthening sustainability certification and environmental governance to support competitive and environmentally responsible palm oil development in Riau Province.